Influence of tumor-associated macrophages and HLA class I expression according to HPV status in head and neck cancer patients receiving chemo/bioradiotherapy. (January 2019) - Ou, Dan; Adam, Julien; Garberis, Ingrid; Blanchard, Pierre; Nguyen, France; Levy, Antonin; Casiraghi, Odile; Gorphe, Philippe; Breuskin, Ingrid; Janot, François; Temam, Stephane; Scoazec, Jean-Yves; et al.
Highlights: Intraepithelial macrophage density was associated with favorable progression-free survival. HLA class I down-regulation was not an independent prognostic factor. Stromal M2 density may potentially be used to guide treatment selection. Abstract: Background and purpose: To investigate the prognostic value of tumor-associated macrophages (TAM) and HLA class I expression according to HPV status in patients with head and neck squamous cell carcinoma treated with definitive radiotherapy combining cisplatin (CRT) or cetuximab (BRT). Material and methods: Ninety-five patients were enrolled. The density of CD68+ cells and CD68+ CD163+ cells (further referred as M2) in the intraepithelial and the stromal compartments, respectively, as well as HLA class I expression in tumor cells, were evaluated semi-quantitatively. Correlations between biomarker expression and treatment outcomes were analyzed. Results: Multivariate analysis showed that the intraepithelial macrophage density (IEMD) was prognostic for favorable progression-free survival (PFS) and there was a non-significant trend for improved overall survival (OS). HLA class I down-regulation was not an independent prognostic factor. Subgroup analysis showed that in p16+ population, patients with high IEMD had improved 5-year PFS vs. patients with low IEMD (81.2% vs. 25.0%, p  < 0.001), while in p16− population, no difference was observed. Similarly, when stratified by primary tumor site, IEMD showed prognostic value in oropharyngeal cancer patients (OPC) but not non-OPC patients. Five-year PFS of patients with low stromal M2 macrophage density treated with CRT was significantly improved vs. those with BRT (54.5% vs. 36.1%, p  = 0.03), while in tumors with high M2, there was no significant difference (50.3% vs. 42.9%, p  = 0.67). Conclusions: The prognostic role of TAM phenotype and distribution depends on HPV status and might predict treatment response. They prompt further validation in prospective studies.